American Matchmaker - Ulmer, Edgar G.; Contner, J. Burgi; Fuchs, Leo; Abarbanell, Judith; Dubinsky, Judel
Leo Fuchs, known on Second Avenue as "the Yiddish Fred Astaire", plays an elegant and eligible bachelor who can never seem to close the marriage deal. Edgar G. Ulmer's last Yiddish movie was also his most modern, an art deco romantic comedy about male ambivalence and Jewish assimilation. With its urbane, neurotic hero, "American Matchmaker" looks ahead to the films of Woody Allen. [jewishfilm.org]